Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Answer =0
lets proceed if a,b,c,d,e are in AP then
(b-a)=(c-b)=(d-c)=(e-d) lets say = t
now b-a  = e-d we get a+e = b+d now put this value in given eqn
a+e -4b +6c -4d  = b+d -4b -4d +6c
eqn becomes
-3b -3d +6c 
now rearrange it
(c-b) + (c-b) + (c-b) +(c-d)+(c-d)+(c-d)
t+t+t -t -t -t =0      (since c-b =t and d-c=t therefore c-d = -t)
Mark it as brainliest answer
1 1 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts